Role of Interventional Radiology in the Management of Liver Transplant Complications in Children - Shah, Ritu; Sharma, Pareena; Variyam, Darshan; Leshen, Michael; Bertino, Frederic J.; Zavaletta, Vaz; Shah, Jay (Digestive Disease Interventions, 2024)
Liver transplantation (LT) is a common solid organ transplant in the pediatric population. The common indications for LT, as well as its complications, differ between adults and children. This difference necessitates unique pediatric interventional radiology (IR) interventions. This article focuses on unique vascular complications occurring post-pediatric LT and highlights the importance of IR in their management. It explores IR's involvement in the workup of patients' pre-LT and management of complications following portosystemic shunts. We discuss advantages and disadvantages of different access routes as well as the prevalence, clinical picture, diagnosis, and management of complications after pediatric LT. These complications encompass portal vein stenosis, portal vein thrombosis, hepatic artery stenosis, hepatic artery thrombosis, hepatic artery pseudoaneurysm, arterioportal fistula, hepatic vein stenosis, and inferior vena cava stenosis. The choice of endovascular technique for a clinical indication depends on vascular anatomy, time since LT, and patient-specific factors. Transsplenic access is a useful alternative to transhepatic or transjugular access. The decision to place a stent in a child is influenced by the expected growth of the child and risk of focal narrowing at stent edge (because of recipient growth). Technical challenges in pediatric patient management, including uncooperative patients and sedation issues, must be considered. Pediatric LT complications can present with significant challenges in the posttransplant care of recipients and may lead to serious morbidity and graft failure if not managed effectively. IR techniques like balloon angioplasty, stent placement, thrombolysis, and embolization have demonstrated success in treating these complications, improving patient outcomes, and reducing long-term morbidity and mortality. By enhancing the understanding of medical practitioners and interventional radiologists about complex vascular complications, this article aims to contribute to better posttransplant care and improved outcomes for LT in pediatric populations. Continued collaboration between specialties and research will advance the field of pediatric LT and IR, to create even more effective treatment strategies.
Keywords: pediatric interventional radiology; pediatric liver transplantation; liver transplantation; complications